Hyper-Enriched Anti-RSV Immunoglobulins Nasally Administered: A Promising Approach for Respiratory Syncytial Virus Prophylaxis - Jacque, Emilie; Chottin, Claire; Laubreton, Daphné; Nogre, Michel; Ferret, Cécile; de Marcos, Sandrine; Baptista, Linda; Drajac, Carole; Mondon, Philippe; De Romeuf, Christophe; Rameix-Welti, Marie-Anne; Eléouët, Jean-François; et al. (Frontiers in Immunology, 2021)
Respiratory syncytial virus (RSV) is a public health concern that causes acute lower respiratory tract infection. So far, no vaccine candidate under development has reached the market and the only licensed product to prevent RSV infection in at-risk infants and young children is a monoclonal antibody (Synagis®). Polyclonal human anti-RSV hyper-immune immunoglobulins (Igs) have also been used but were superseded by Synagis® owing to their low titer and large infused volume. Here we report a new drug class of immunoglobulins, derived from human non hyper-immune plasma that was generated by an innovative bioprocess, called Ig cracking, combining expertises in plasma-derived products and affinity chromatography. By using the RSV fusion protein (F protein) as ligand, the Ig cracking process provided a purified and concentrated product, designated hyper-enriched anti-RSV IgG, composed of at least 15-20% target-specific-antibodies from normal plasma. These anti-RSV Ig displayed a strong in vitro neutralization effect on RSV replication. Moreover, we described a novel prophylactic strategy based on local nasal administration of this unique hyper-enriched anti-RSV IgG solution using a mouse model of infection with bioluminescent RSV. Our results demonstrated that very low doses of hyper-enriched anti-RSV IgG can be administered locally to ensure rapid and efficient inhibition of virus infection. Thus, the general hyper-enriched Ig concept appeared a promising approach and might provide solutions to prevent and treat other infectious diseases.